Can Excessive Consumption of Celery Threaten Continuation of pregnancy: a Biometrical and Histopathological Study of Mice Placenta - Mojgan Moshrefi; Seyyed Kazem Bazazzadeh; Morteza Anvari; Maryam Yadegari Dehnavi; Naeimeh Akramzadeh Ardakani; Abbas Shahedi (Journal of Kerman University of Medical Sciences, 2022)
Background: Placenta has a strategic role in fetal/maternal exchange. A healthy placenta is essential for normal fetal development. Avoiding consumption of some foods and vegetables is suggested during pregnancy due to the risk of placental disorders. Celery is a high consumed vegetable that some studies concern about its adverse effect on pregnancy. The present study focused on its consumption side effects in different trimesters of gestation on mouse placenta.Methods: Duration of pregnancy in mice is three weeks. Five groups of 5 mice were considered. Groups I, II and III received celery hydro-alcoholic extract only during the 1st, 2nd and 3rd weeks of pregnancy, respectively and group IV received it during all the weeks of gestation. The 5th group was considered as control and just received placebo. The biometrical sizes of placenta (weight, length and diameter) were measured and histopathological analysis was done.Results: Celery consumption decreased the weight of placenta in groups II, III and IV. Also, placental length and diameter decreased in groups I and IV. Histopathological examination showed decrease of placenta trophoblastic giant cells and increase of trophoblast glycogen cells in the basal layer. Generally, morphological and pathological changes in the 4th group showed more deviations from the control group. Basal and Labyrinth layer thickness decreased in the experimental groups. Also, hyperaemia was observed in labyrinth layer of the experimental groups.Conclusion: Due to the decrease of placenta biometrical sizes and histo-pathological adverse effects, it is advised that celery should be used with more precaution, during pregnancy.